Estudo para aproveitamento de energia em bancada de teste de caixa de câmbio - Almeida, Jamardo Torres de (Universidade do Vale do Rio dos Sinos, 2014)
The gearbox is one of the principal components of tractors. In the development of a gearbox project, there are steps for testing and evaluating its performance. These tests can be conducted either in the field or in the laboratory. The aim of this work is to develop a project for energy efficiency in gearbox tests performed in laboratory. With new components being added to the current concept of bench testing, such as speed multiplier, electricity generators and converters, the proposed system will provide a recovery of part of the electrical energy used during the tests execution. The mechanical power wasted will be utilized by engaging the new components to the rear axle of the test bench, so that, a significant amount of energy used in the test be recovered and returned to the main engine. Two different possible configurations bench for energy recovery were proposed. One of the test bench systems, where different components, in addition to the gearbox, can be tested, showed a payback of 7.6 years, corresponding to an annual financial reduction of R$ 277,816.00. The bench system where only gearboxes are tested, showed a payback of 3.3 years, corresponding to an annual reduction of financial R$ 312,190.00.
Keywords: Reaproveitamento de energia; Bancada de teste; Caixa de câmbio; Dinamômetro; ACCNPQ::Engenharias::Engenharia Mecânica